Doubles and images of Twins : an approach to West African portrait studio photography - (:unkn) unknown (My University, 2009)
Despite evident cultural differences, we can nevertheless notice great similarities in many West African countries. In studio windows, double portraits - photographs of two similar or identical figures - are often displayed. In the case of the similar figures, an attempt is made to create a twin-like resemblance between two different people. When the figures are identical, one person has been reproduced twice on the same print as if he or she was next to a twin. Though acknowledged to some extent by anthropologists and historians, research on West Africa studio photography has never approached double portraits in photography as a specific aesthetic production. Widespread for several decades, more than mere entertainment, a passing fad or a commercial strategy and suggesting links with cultural meanings, they are an artistic phenomenon worthy of historical art analysis. This thesis explores the subject. It is based on a collection of three hundred photographs dating from the 1970s up to the present day, collected from a hundred photographers in four sub-Saharan countries (Togo, Benin, Burkina Faso and Mali), and informed by studio customers, locals, and people involved in the cultural life. The double portraits are thus analyzed in regard to their contexts of both production and reception. They are also studied as index and icons, raising questions on representation, likeness and aesthetic values, which are the specific issues of the art of the double. They are discussed according to the local definitions of beings, then situated within a history of African sculpture and photography and in a more comprehensive history of double and twin portraits between Europe and Africa. They will finally be contextualized through a collective imagination of “twinness” of which they are the seeds and fruits ; an imagination - as a whole range of visual and conceptual images - inspired by myths and practices related to twinship in these countries where the twin bir
Keywords: African Research